Penetration depth of cold atmospheric plasma into biological tissue: a review - Jiang, Dong; Zhang, Jiashuo; Liu, Zhixin; Yu, Yilin; Xiao, Li; Ai, Mi; Luo, Ming; Yu, Ollie Yiru; Cao, Yingguang; Song, Ke (Frontiers in Bioengineering and Biotechnology, 2026)
Cold atmospheric plasma (CAP) is a non-thermal plasma generated near room temperature that has broad medical applications in the medical field, including antitumor, antimicrobial, and anti-inflammatory effects, promotion of tissue regeneration, and enhancement of transdermal and mucosal drug delivery. However, there is currently a lack of standardization regarding the indications for CAP and its application parameters, resulting in varying degrees of histological penetration depths reported in different studies. Therefore, to further promote the safe and effective clinical application of CAP, the histological levels at which CAP can be applied must be clearly defined. Here, we review the depth of tissue penetration achieved by CAP under various conditions and analyze the key factors influencing penetration depth, using this knowledge to propose how these factors should be adjusted for different application requirements to achieve safer and more precise therapies.